FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN PEMILIK KOS DALAM MEMBAYAR PAJAK RUMAH KOS: Studi Kasus Pada Pemilik Usaha Kos-Kosan di Kota Kupang - Dhano, Elisabeth D; Banda, Falentina L; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2021)
This study aims to determine the effect of taxpayer awareness, taxpayer knowledge, tax sanctions and tax service services on tax compliance. This research was conducted in the city of Kupang, descriptive statistical research method through a quantitative approach. The population in this study are taxpayers who carry out business activities for boarding houses in Kupang City. Sampling is in accordance with the provisions of the sample from a certain population that is the easiest to reach or obtain, for example the one closest to the place where the researcher is domiciled. The results of this study prove that a) Taxpayer awareness has no effect on tax compliance of boarding house owners in the city of Kupang. It is proven by a significance value of 0.841 > from a value of 0.05, b) Taxpayer knowledge has an effect on tax compliance of boarding house owners in the city of Kupang. It is proven by a significance value of 0.000 < from the value of sig 0.05, c) Tax sanctions have no effect on tax compliance of boarding house owners in the city of Kupang. It is proven by a significance value of 0.430 > from the value of sig 0.05 and d) Fiscal Services does not affect the tax compliance of boarding house owners in the city of Kupang. It is proven by a significance value of 0.430 > from the value of sig 0.05.